Frameworks towards a virtual co-creation tool for fuzzy front-end of service development in health care context - Lahtinen Katriina; Aaltonen Satu; Järvinen Marika; Teittinen Outi; Pirttimäki Mikko (Denmark, 2022)
This paper combines entrepreneurial behaviour and innovation with design thinking in order to investigate the use of the IdeaWindow, the ict-based tool planned for employee-driven service development, in a health care organisation. The tool enables participation of heterogeneous group of people to fuzzy front-end of service development. The paper asks how virtual tool can be used for tackling the unknown - tacit knowledge, hidden possibilities and initiatives in this context. What kind of perspectives and topics the employees bring up when using a virtual tool in the front-end of service development. The results are based on IdeaWindow entries and electronic survey data collected in Finnish hospital ward.
The 25th Annual RESER Conference ”Innovative Services in the 21st Century” Proceedings